PENGARUH PEMBIASAAN IBADAH TERHADAP AKHLAK SISWA SMP - Ajeng Putri Wulandari; Didit Darmawan (TEACHER : Jurnal Inovasi Karya Ilmiah Guru, 2026)
Concerns regarding the decline in ethical standards amongst secondary school pupils—particularly in terms of lax discipline and a waning sense of care—have been the primary impetus for schools to begin incorporating spiritual practices into their character-building programmes. This article seeks to re-examine the findings of ten previous studies to assess the extent to which these spiritual routines can actually refine pupils’ behaviour. By employing a literature review and analysing the content of relevant articles, a fairly clear pattern emerges: activities such as regular congregational prayer or the Dhuha prayer do indeed bring a breath of fresh air, fostering a shift in pupils’ attitudes towards a more positive direction. However, an interesting finding is that this effect does not occur automatically. Its success is largely determined by how the school manages the programme, the strength of the example set by teachers, and the support from the surrounding community. Indeed, there is one unique finding suggesting that regular Dhuha prayer does not always correlate directly with exam grades, proving that moral matters and academic performance follow their own distinct paths. The conclusion of this review suggests that schools should not merely establish a prayer timetable, but also foster close cooperation with parents and create a comprehensive religious atmosphere so that the results truly leave a lasting impression on the students’ souls. ABSTRAK Kegelisahan mengenai merosotnya etika remaja di lingkungan SMP terutama soal disiplin yang kendor serta pudarnya rasa peduli menjadi titik tolak utama mengapa sekolah-sekolah mulai mencoba menyisipkan rutinitas ibadah ke dalam agenda pembentukan karakter. Tulisan ini mencoba menelaah kembali jejak-jejak dari sepuluh hasil riset terdahulu guna melihat sejauh mana sebenarnya rutinitas spiritual ini mampu memoles perilaku para siswa. Dengan mengandalkan metode studi literatur dan membedah isi artikel-artikel yang relevan, terlihat sebuah pola yang cukup jelas: kegiatan seperti shalat berjamaah atau dhuha yang dilakukan terus-menerus memang membawa angin segar bagi perubahan sikap siswa ke arah yang lebih positif. Namun, temuan yang menarik adalah efek ini ternyata tidak terjadi secara otomatis. Keberhasilannya sangat ditentukan oleh bagaimana sekolah mengelola program tersebut, seberapa kuat teladan yang diberikan bapak-ibu guru, hingga dukungan dari lingkungan sekitar. Bahkan, ada satu temuan unik yang menunjukkan bahwa rajin shalat dhuha tidak selalu berbanding lurus dengan nilai ujian di kelas, yang membuktikan bahwa urusan moral dan nilai akademis punya jalurnya masing-masing. Kesimpulan dari tinjauan ini menyarankan agar sekolah tidak hanya sekadar membuat jadwal ibadah, tapi juga membangun kerja sama yang erat dengan orang tua dan menciptakan suasana religius yang menyeluruh agar hasilnya benar-benar membekas pada jiwa siswa.